(untitled) (Scientific journal of the Fergana State University, 2023)
This article provides information that currently the nature of the world and our country is changing as a result of anthropogenic influences, as a result of these changes, various changes are observed in all landscape complexes of nature, as well as natural-anthropogenic landscape complexes as a result of the development of new lands, as well as environmental problems such as desertification, salinity, degradationMeasures to eliminate these environmental problems are also outlined.